Marginal bone loss around platform-switched and platform-matched implants following immediate dental implant placement - Systematic Review - Jiten Vaghela; Mohammad-Adel Moufti; Noha Seoudi; Waad Kheder (Elsevier, 2024)
Objective: This study aimed to examine marginal bone loss (MBL) around immediately placed platform-switched implants (PS) compared to platform-matched (PM) implants; and to critically appraise the available literature on this topic. Materials and Methods: Randomized control trials (RCTs), non- randomized control trials (NRCT) and case series of immediate placement platform-switched and platform-matched implant, published in English were included in the study. Two databases, namely Medline and PubMed covering the period between July 1966 and July 2023 were searched. A total of five case series, five RCTs and one NRCT were included in this systematic review by using pre-defined study selection criteria and following the PRISMA protocol. A critical appraisal of the selected studies was completed using standardized appraisal checklists, including CASP tool for critical appraisal of RCTs, the Downs and Black checklist for NRCT, and the CEBMa checklist for case series studies. Results: Five studies showed a statistically significant difference in MBL (PS: 0.18-0.78 mm, PM 0.51-1.19 mm). The studies featured a small sample size, and substantial methodological variability in patients' selection criteria, implant and abutment designs, connection types and surgical protocols. A high risk of bias was identified, especially in case series studies. Conclusion: The use of PS implants in immediate placement protocols can lead to a statistically significant reduction in MBL compared to PM implants. However, the results need to be interpreted with caution, given the numerous confounding variables and clinical heterogeneity existing between the studies.